Effects of Temperature Treatments on Cytosine-Methylation Profiles of Diploid and Autotetraploid Plants of the Alpine Species Ranunculus kuepferi (Ranunculaceae) - Syngelaki, Eleni (Front Plant Sci, 2020)
The exposure to environmental stress can trigger epigenetic variation, which may have several evolutionary consequences. Polyploidy seems to affect the DNA methylation profiles. Nevertheless, it abides unclear whether temperature stress can induce methylations changes in different cytotypes and to what extent a treatment shift is translated to an epigenetic response. A suitable model system for studying these questions is Ranunculus kuepferi, an alpine perennial herb. Diploid and autotetraploid individuals of R. kuepferi were exposed to cold (+7°C day/+2°C night; frost treatment −1°C cold shocks for 3 nights per week) and warm (+15° day/+10°C night) conditions in climate growth chambers for two consecutive flowering periods and shifted from one condition to the other after the first flowering period. Methylation-sensitive amplified fragment-length polymorphism markers were applied for both years, to track down possible alterations induced by the stress treatments. Patterns of methylation suggested that cytotypes differed significantly in their profiles, independent from year of treatment. Likewise, the treatment shift had an impact on both cytotypes, resulting in significantly less epiloci, regardless the shift's direction. The AMOVAs revealed higher variation within than among treatments in diploids. In tetraploids, internally-methylated loci had a higher variation among than within treatments, as a response to temperature's change in both directions, and support the hypothesis of temperature stress affecting the epigenetic variation. Results suggest that the temperature-sensitivity of DNA methylation patterns shows a highly dynamic phenotypic plasticity in R. kuepferi, as both cytotypes responded to temperature shifts. Furthermore, ploidy level, even without effects of hybridization, has an important effect on epigenetic background variation, which may be correlated with the DNA methylation dynamics during cold acclimation.